AN ANALYSIS OF TABOO WORDS USED BY CHARACTERS IN FREEDOM WRITERS MOVIE - TRULYFIONA, TIARA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Trulyfiona, Tiara. 2013. An Analysis Of Taboo Words Used by Characters in Freedom Writter Movie. Study Program of English, Universitas Brawijaya. Supervisor : Endang Sasanti; Co – Supervisor : Muhammad Rozin.Keywords : Sociolinguistics, taboo words, “freedom writer” movie, four ethnic groups.Sociolinguistics  is  the  study  of  language  in  relation  to  society,  it  is concerned with  investaging the relationship between society and language. There are many majors of Sociolinguistics, but this study only concerns with one major Sociolinguistics. It is taboo words.  Taboo  is  one  study  of Sociolinguistics  that  has  relation with  culture  and society. Taboo  is  a part of  language  and  language  itself  is a part of human  life. Nowadays,  taboo words  can  be  found  easily  in  our  environment.  For  example, “Freedom Writer” movies,  there  are  some  taboo words  that  are  uttered  by  the characters  in  this movie. This  research only  focused on  the  type of  taboo words and  the  purpose  of  using  taboo  words  by  the  characters.  The  purpose  of  this research  is  to  find out  the  types of  taboo words  and  the purpose of using  taboo words by the characters. In  analyzing  the  type  of  taboo  utterances,  the writer  uses  the  theory  of Wardaugh  (1986).  In  analyzing  the  factors  affecting  of  using  taboo words,  the writer  uses  the  theory  of Holmes  (1992).  The  characters  consist  of  four  ethnic groups,  they are African  - Americans, Hispanics, Asians and white. After doing the analysis, the writer found 39 taboo utterances by African - Americans, 7 taboo utterances by Hispanics, 6  taboo utterances by Asians, and 2  taboo utterances by White people. After analyzing  the  taboo words used by  the  character,  the writer found out that most African - American using taboo words because of their Status social, the writer found out the factors affecting them use taboo words. The writer also  found  that  the  type  of  taboo  words  that  are mostly  uttered  are  excertion, bodily function and religious matter terms.     The writer hopes that next linguistic student conduct research taboo words involved not only in violence but might also in the other condition. It can be used to compare taboo word in different atmosphere. The writer also suggests using other object to research. It is not only in the movie but it can be in the poem or song. She also suggests the next researcher to use different theories and methods if they want to conduct similar research.